Relations of drug use and socioeconomic factors with adherence to dental treatment among adolescents - Sílvia Letícia Freddo; Inara Pereira da Cunha; Jaqueline Vilela Bulgareli; Yuri Wanderley Cavalcanti; Antonio Carlos Pereira (BMC, 2018)
Abstract Background Adolescents are vulnerable to behaviors that weaken health, by adopting habits that interfere with adherence to treatment. The aims of the present study were to investigate adolescents' adherence to dental treatment and the relations between this behavior and socioeconomic factors and consumption of licit and illicit chemical substances. Methods A longitudinal study was conducted with 474 adolescents from Piracicaba/SP/Brazil, who initially underwent a dental examination to verify the adherence for dental treatment. After 18 months, 325 adolescents were reassessed. Valid questions about socioeconomic conditions and use of alcohol and drugs were applied to participants. The chi-square test and Fisher's exact test were used. The prevalence ratios were estimated with the respective 95% confidence intervals, using generalized linear models with Poisson distribution. Results Eighteen (18) months after the first consultation, 325 adolescents were reassessed: 161 (49%) did not adhere to the treatment, and 164 (51%) adhered to it and answered the socioeconomic and alcohol and illicit drug questionnaires. Their mean age was 15 ± 1 years; of them, 189 (58%) were female. The prevalence of adherence to treatment decreased in patients without their own home (p = 0.034). In the individual analysis of the variables, drinking alcohol alone, experimenting with drugs, and proximity of friends who consumed illicit substances were associated with the outcome (p < 0.05). However, in the joint analysis, only proximity of friends who consumed drugs was the factor related to low adherence to dental treatment among the adolescents (p = 0.035). Conclusion Adolescents who consumed alcohol and socialized with friends who used illicit drugs had greater difficulty in adhering to dental treatment.